Integrative network analysis revealed the molecular function of folic acid on immunological enhancement in a sheep model - Wang, Bing; Li, Heqiong; Li, Zhen; Wang, Bo; Zhang, Han; Zhang, Boyan; Luo, Hailing (Frontiers in Immunology, 2022)
We previously observed the beneficial role of folic acid supplemented from maternal or offspring diet on lamb growth performance and immunity. Twenty-four Hu lambs from four groups (mother received folic acid or not, offspring received folic acid or not) were used in the current study, which was conducted consecutively to elucidate the molecular regulatory mechanisms of folic acid in lambs by analyzing blood metabolome, liver transcriptome, and muscle transcriptome. Serum metabolomics analysis showed that L-homocitrulline, hyodeoxycholic acid, 9-Hpode, palmitaldehyde, N-oleoyl glycine, hexadecanedioic acid, xylose, 1,7-dimethylxanthine, nicotinamide, acetyl-N-formyl-5-methoxykynurenamine, N6-succinyl adenosine, 11-cis-retinol, 18-hydroxycorticosterone, and 2-acetylfuran were down-regulated and methylisobutyrate was up-regulated by the feeding of folic acid from maternal and/or offspring diets. Meanwhile, folic acid increased the abundances of S100A12 and IRF6 but decreased TMEM25 in the liver. In the muscle, RBBP9, CALCR, PPP1R3D, UCP3, FBXL4, CMBL, and MTFR2 were up-regulated, CYP26B1 and MYH9 were down-regulated by the feeding of folic acid. The pathways of bile secretion, biosynthesis of unsaturated fatty acids, linoleic acid metabolism, and herpes simplex virus 1 infection were changed by folic acid in blood, liver, or muscle. Further integrated analysis revealed potential interactions among the liver, blood, and muscle, and the circulating metabolites, hub gene, and pathways, which might be the predominant acting targets of folic acid in animals. These findings provide fundamental information on the beneficial function of folic acid no matter from maternal or offspring, in regulating animal lipid metabolism and immune enhancement, providing a theoretical basis for the use of folic acid from the view of animal health care.